```
class Mse():
def __call__(self, inp, targ):
self.inp,self.targ = inp,targ
self.out = mse(inp, targ)
return self.out
def backward(self):
= self.targ.shape[0]
N = self.inp
A = self.targ
Y = (2./N) * (A.squeeze() - Y).unsqueeze(-1)
dJ_dA self.inp.g = dJ_dA
```

# Motivation

Connect the math to the code for what Jeremy Howard did in his `03_backprop.ipynb`

notebook for the 2022 part 2 course. The simple network for this post is that we have a single neuron followed by a Rectified Linear Unit (ReLU) and then the Mean Squared Error (MSE) loss function.

I know we want to get to many neurons (stacked in multiple layers) but even this simple setting will take us quite far.

# Notation

- \(N\) : number of training examples
- \(d\) : number of features
- \(\mathbf{x}^{(i)}\) is the \(i\)-th training example and can be represented as a column vector \[ \mathbf{x}^{(i)} = \begin{bmatrix} x^{(i)}_1 \\ x^{(i)}_2 \\ \vdots \\ x^{(i)}_d \end{bmatrix} \]
- \(\mathbf{w}\) is the vector of weights for a single neuron \[ \mathbf{w} = \begin{bmatrix} w_1 \\ w_2 \\ \vdots \\ w_d \end{bmatrix} \]
- \(b\) is the bias term for a single neuron
- \(\mathbf{X}\) is an \(N \times d\) matrix with the training examples stacked in rows \[ \mathbf{X} = \begin{bmatrix} x^{(1)}_1 & x^{(1)}_2 & \cdots & x^{(1)}_d\\ x^{(2)}_1 & x^{(2)}_2 & \cdots & x^{(2)}_d\\ \vdots & \vdots & \ddots & \vdots\\ x^{(N)}_1 & x^{(N)}_2 & \cdots & x^{(N)}_d \end{bmatrix} \]
- \(\{y^{(i)}\}_{i=1}^{N}\) are the targets for each of the \(N\) training examples
- \(z^{(i)}\) is the output of our single neuron when the \(i\)-th training example is passed through it
- Specifically, \(z^{(i)} = \mathbf{w}^T\mathbf{x}^{(i)} + b = b + \sum_{j=1}^{d}w_{j}x^{(i)}_{j} = b + w_{1}x^{(i)}_{1} + \ldots + w_{j}x^{(i)}_{j} + \ldots + w_{d}x^{(i)}_{d}\). Additionally we see that,
- \(\frac{\partial z^{(i)}}{\partial w_{j}} = x^{(i)}_{j}\)
- \(\frac{\partial z^{(i)}}{\partial b} = 1\)
- \(\frac{\partial z^{(i)}}{\partial x^{(i)}_{j}} = w_{j}\)

- Specifically, \(z^{(i)} = \mathbf{w}^T\mathbf{x}^{(i)} + b = b + \sum_{j=1}^{d}w_{j}x^{(i)}_{j} = b + w_{1}x^{(i)}_{1} + \ldots + w_{j}x^{(i)}_{j} + \ldots + w_{d}x^{(i)}_{d}\). Additionally we see that,
- \(a^{(i)} = \phi(z^{(i)})\) is the activation when an input \(z^{(i)}\) is passed through an activation function \(\phi\)
- \(\{a^{(i)}\}_{i=1}^{N}\) are the activations for each of the \(N\) training examples when passed through a single neuron followed by the application of the activation function
- For the purposes of this page the activation function is considered to be a ReLU so \[ a^{(i)} = \phi(z^{(i)}) = \max\{0, z^{(i)}\} = \begin{cases} z^{(i)} & z^{(i)} \gt 0 \\ 0 & z^{(i)} \leq 0 \end{cases} \]

# Gradients

## Gradient of loss with respect to the Activations \(a^{(i)}\)

\(J\left(\{y^{(i)}\}_{i=1}^{N},\{a^{(i)}\}_{i=1}^{N}\right) = \frac{1}{N}\sum_{i=1}^{N}(y^{(i)}-a^{(i)})^{2}\) is the loss (mean squared error) across the \(N\) training examples

The `backward`

function of the `Mse`

class computes an estimate of how the loss function changes as the input activations change.

The change in the loss as the \(i\)-th activation changes is given by

\[\frac{\partial J}{\partial a^{(i)}} = \frac{2}{N}\sum_{i=1}^{N} \frac{\partial (y^{(i)}-a^{(i)})^{2}}{\partial a^{(i)}} = \frac{2}{N}(y^{(i)}-a^{(i)})\frac{\partial (y^{(i)}-a^{(i)}) }{\partial a^{(i)}} = \frac{2}{N}(a^{(i)}-y^{(i)})\]

where the last step follows because \(\frac{\partial (y^{(i)}-a^{(i)}) }{\partial a^{(i)}} = 0-1 =-1\).

The change in the loss as a function of the change in activations from our training examples is captured by the \(N \times 1\) matrix:

\[ \frac{\partial J}{\partial \mathbf{a}} = \begin{bmatrix} \frac{\partial J}{\partial a^{(1)}} \\ \frac{\partial J}{\partial a^{(2)}} \\ \vdots \\ \frac{\partial J}{\partial a^{(N)}} \end{bmatrix} = \begin{bmatrix} \frac{2}{N}\left(a^{(1)}-y^{(1)}\right) \\ \frac{2}{N}\left(a^{(2)}-y^{(2)}\right) \\ \vdots \\ \frac{2}{N}\left(a^{(N)}-y^{(N)}\right) \end{bmatrix} \]

From the implementation perspective, the activations \(\{a^{(i)}\}_{i=1}^{N}\) and the targets \(\{y^{(i)}\}_{i=1}^{N}\) are passed in and stored during the forward pass (specifically in the dunder `__call__`

method). In the backward pass these are retrieved and \(\frac{\partial J}{\partial \mathbf{a}}\) is computed and stored for access by the `backward`

function of the prior layer. Hopefully the `backward`

method for the `Mse`

class makes sense now.

## Gradient of loss with respect to the Linear Output \(z^{(i)}\)

```
class Relu():
def __call__(self, inp):
self.inp = inp
self.out = inp.clamp_min(0.)
return self.out
def backward(self):
= self.out.g
dJ_dA = (self.inp>0).float()
dA_dZ
# Note this is an elementwise multiplication
= dJ_dA * dA_dZ
dJ_dZ
self.inp.g = dJ_dZ
```

How does the loss change as the output of the linear unit changes?

\[\frac{\partial J}{\partial z^{(i)}} = \frac{\partial J}{\partial a^{(i)}} \frac{\partial a^{(i)}}{\partial z^{(i)}} = \frac{2}{N}\left(a^{(i)}-y^{(i)}\right)\frac{\partial a^{(i)}}{\partial z^{(i)}}\]

For the ReLU activation function we have that, \[ \frac{\partial a^{(i)}}{\partial z^{(i)}} = \begin{cases} 1 & z^{(i)} \gt 0 \\ 0 & z^{(i)} \leq 0 \end{cases} \]

and hence

\[\frac{\partial \mathbf{a}}{\partial \mathbf{z}} = \begin{bmatrix} \frac{\partial a^{(1)}}{\partial z^{(1)}} \\ \frac{\partial a^{(2)}}{\partial z^{(2)}} \\ \vdots \\ \frac{\partial a^{(N)}}{\partial z^{(N)}} \end{bmatrix} \]

Thus the change in the loss as a function of the change in the output from the linear unit on our training examples is given by the \(N \times 1\) matrix:

\[ \frac{\partial J}{\partial \mathbf{z}} = \begin{bmatrix} \frac{\partial J}{\partial z^{(1)}} \\ \frac{\partial J}{\partial z^{(2)}} \\ \vdots \\ \frac{\partial J}{\partial z^{(N)}} \end{bmatrix} = \begin{bmatrix} \frac{\partial J}{\partial a^{(1)}}\frac{\partial a^{(1)}}{\partial z^{(1)}} \\ \frac{\partial J}{\partial a^{(2)}}\frac{\partial a^{(2)}}{\partial z^{(2)}} \\ \vdots \\ \frac{\partial J}{\partial a^{(N)}}\frac{\partial a^{(N)}}{\partial z^{(N)}} \end{bmatrix} \]

So \(\frac{\partial J}{\partial \mathbf{z}}\) ends up being an elementwise product between the corresponding entries of \(\frac{\partial J}{\partial \mathbf{a}}\) and \(\frac{\partial \mathbf{a}}{\partial \mathbf{z}}\).

From the implementation perspective, in the backward pass \(\frac{\partial \mathbf{a}}{\partial \mathbf{z}}\) will be computed locally and multiplied elementwise with \(\frac{\partial J}{\partial \mathbf{a}}\) (this will have been computed in the backward pass in the `Mse`

class and will be available to access when the backward function of the `Relu`

function is called).

## Gradient of loss with respect to \(w_{j}, b\) and \(X\)

The next three subsections will explain the `backward`

function of the `Lin`

class.

```
class Lin():
def __init__(self, w, b): self.w,self.b = w,b
def __call__(self, inp):
self.inp = inp
self.out = lin(inp, self.w, self.b)
return self.out
def backward(self):
# See Gradient of loss with respect to w_j
= self.out.g
dJ_dZ = self.inp
X = X.t() @ dJ_dZ
dJ_dW self.w.g = dJ_dW
# See Gradient of loss with respect to the bias b
= dJ_dZ.sum(0)
dJ_db self.b.g = dJ_db
# See Gradient of loss with respect to X
= dJ_dZ @ self.w.t()
dJ_dX self.inp.g = dJ_dX
```

### Gradient of loss with respect to \(w_{j}\)

How does the loss react when we wiggle \(w_{j}\)? \[\frac{\partial J}{\partial w_{j}} = \frac{\partial J}{\partial \mathbf{z}} \frac{\partial \mathbf{z}}{\partial w_{j}}= \sum_{i=1}^{N}\frac{\partial J}{\partial z^{(i)}} \frac{\partial z^{(i)}}{\partial w_{j}} = \frac{\partial J}{\partial z^{(1)}}x^{(1)}_{j} + \frac{\partial J}{\partial z^{(2)}}x^{(2)}_{j} + \ldots + \frac{\partial J}{\partial z^{(N)}}x^{(N)}_{j}\]

Thus,

\[ \frac{\partial J}{\partial \mathbf{w}} = \begin{bmatrix} \frac{\partial J}{\partial w_{1}} \\ \frac{\partial J}{\partial w_{2}} \\ \vdots \\ \frac{\partial J}{\partial w_{d}} \end{bmatrix} = \begin{bmatrix} x^{(1)}_{1}\frac{\partial J}{\partial z^{(1)}} + x^{(2)}_{1}\frac{\partial J}{\partial z^{(2)}} + \ldots + x^{(N)}_{1}\frac{\partial J}{\partial z^{(N)}} \\ x^{(1)}_{2}\frac{\partial J}{\partial z^{(1)}} + x^{(2)}_{2}\frac{\partial J}{\partial z^{(2)}} + \ldots + x^{(N)}_{2}\frac{\partial J}{\partial z^{(N)}} \\ \vdots \\ x^{(1)}_{d}\frac{\partial J}{\partial z^{(1)}} + x^{(2)}_{d}\frac{\partial J}{\partial z^{(2)}} + \ldots + x^{(N)}_{d}\frac{\partial J}{\partial z^{(N)}} \end{bmatrix} \]

This is a matrix multiplication in disguise (each row is a dot product) and can be written more compactly as:

\[ \frac{\partial J}{\partial \mathbf{w}} = \begin{bmatrix} x^{(1)}_1 & x^{(2)}_1 & \cdots & x^{(N)}_1\\ x^{(1)}_2 & x^{(2)}_2 & \cdots & x^{(N)}_2\\ \vdots & \vdots & \ddots & \vdots\\ x^{(1)}_d & x^{(2)}_d & \cdots & x^{(N)}_d \end{bmatrix} \begin{bmatrix} \frac{\partial J}{\partial z^{(1)}} \\ \frac{\partial J}{\partial z^{(2)}} \\ \vdots \\ \frac{\partial J}{\partial z^{(N)}} \end{bmatrix} =\mathbf{X}^{T}\frac{\partial J}{\partial \mathbf{z}} \]

From the implementation perspective \(\mathbf{X}^{T}\) is computed locally in the `backward`

function of the `Lin`

class while \(\frac{\partial J}{\partial \mathbf{z}}\) is ready and waiting to be accessed. Recall the latter was computed in the `backward`

function of the `Relu`

class.

### Gradient of loss with respect to the bias \(b\)

\[\frac{\partial J}{\partial b} = \frac{\partial J}{\partial \mathbf{z}} \frac{\partial \mathbf{z}}{\partial b}= \sum_{i=1}^{N}\frac{\partial J}{\partial z^{(i)}} \frac{\partial z^{(i)}}{\partial b}= \sum_{i=1}^{N}\frac{\partial J}{\partial z^{(i)}} 1 = \frac{\partial J}{\partial z^{(1)}} + \frac{\partial J}{\partial z^{(2)}} + \ldots + \frac{\partial J}{\partial z^{(N)}}\]

From the implementation perspective we need to access \(\frac{\partial J}{\partial \mathbf{z}}\) and sum across the first axis. The local derivative computation of \(\frac{\partial \mathbf{z}}{\partial b}\) is particulary simple (since each \(\frac{\partial z^{(i)}}{\partial b}\) is just \(1\)).

### Gradient of loss with respect to \(x^{(i)}_{j}\)

Let’s understand how the loss will change as we twiddle the \(j\)-th feature of the \(i\)-th training example.

\[\frac{\partial J}{\partial x^{(i)}_{j}} = \frac{\partial J}{\partial \mathbf{z}} \frac{\partial \mathbf{z}}{\partial x^{(i)}_{j}}= \sum_{k=1}^{N}\frac{\partial J}{\partial z^{(k)}} \frac{\partial z^{(k)}}{\partial x^{(i)}_{j}} = \frac{\partial J}{\partial z^{(i)}}\frac{\partial z^{(i)}}{\partial x^{(i)}_{j}} + \sum_{k: k \neq i}^{N} \frac{\partial J}{\partial z^{(k)}}\frac{\partial z^{(k)}}{\partial x^{(i)}_{j}}\]

Since \(\frac{\partial z^{(k)}}{\partial x^{(i)}_{j}} = 0\) for any \(k \neq i\) we get

\[\frac{\partial J}{\partial x^{(i)}_{j}} = \frac{\partial J}{\partial z^{(i)}}w_{j}\]

Thus the \(N \times d\) matrix of these gradients are,

\[ \frac{\partial J}{\partial \mathbf{X}} = \begin{bmatrix} \frac{\partial J}{\partial x^{(1)}_{1}} & \frac{\partial J}{\partial x^{(1)}_{2}} & \cdots & \frac{\partial J}{\partial x^{(1)}_{d}} \\ \frac{\partial J}{\partial x^{(2)}_{1}} & \frac{\partial J}{\partial x^{(2)}_{2}} & \cdots & \frac{\partial J}{\partial x^{(2)}_{d}} \\ \vdots & \vdots & \ddots & \vdots \\ \frac{\partial J}{\partial x^{(N)}_{1}} & \frac{\partial J}{\partial x^{(N)}_{2}} & \cdots & \frac{\partial J}{\partial x^{(N)}_{d}} \end{bmatrix}= \begin{bmatrix} \frac{\partial J}{\partial z^{(1)}}w_{1} & \frac{\partial J}{\partial z^{(1)}}w_{2} & \cdots & \frac{\partial J}{\partial z^{(1)}}w_{d} \\ \frac{\partial J}{\partial z^{(2)}}w_{1} & \frac{\partial J}{\partial z^{(2)}}w_{2} & \cdots & \frac{\partial J}{\partial z^{(2)}}w_{d} \\ \vdots & \vdots & \ddots & \vdots \\ \frac{\partial J}{\partial z^{(N)}}w_{1} & \frac{\partial J}{\partial z^{(N)}}w_{2} & \cdots & \frac{\partial J}{\partial z^{(N)}}w_{d} \end{bmatrix} \]

More compactly this can be represented as an outer product,

\[ \frac{\partial J}{\partial \mathbf{X}} = \begin{bmatrix} \frac{\partial J}{\partial z^{(1)}} \\ \frac{\partial J}{\partial z^{(2)}} \\ \vdots \\ \frac{\partial J}{\partial z^{(N)}} \end{bmatrix} \begin{bmatrix} w_{1} & w_{2} & \cdots & w_{d} \end{bmatrix} =\frac{\partial J}{\partial \mathbf{z}}\mathbf{w}^{T} \]